2011
DOI: 10.1093/ndt/gfr458
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C virus infection and malnutrition-inflammation complex syndrome in maintenance hemodialysis patients

Abstract: MHD patients with active HCV infections have more severe MICS-associated metabolic and physiological disease than MHD patients without active HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
6
7
0
Order By: Relevance
“…In our study WBC's and platelets were significantly lower in group 1 than group 2. These results are in agreement with Tsai et al, [11] and can be due to replication of the HCV virus in bone marrow, splenic sequestration and immune mediated [14] . Hemoglobin was higher in group 1 and these results are in agreement with Alsaran et al, [15] and can be explained by that hepatic inflammation induces erythropoietin production by liver cells and also due to altered iron metabolism [16] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study WBC's and platelets were significantly lower in group 1 than group 2. These results are in agreement with Tsai et al, [11] and can be due to replication of the HCV virus in bone marrow, splenic sequestration and immune mediated [14] . Hemoglobin was higher in group 1 and these results are in agreement with Alsaran et al, [15] and can be explained by that hepatic inflammation induces erythropoietin production by liver cells and also due to altered iron metabolism [16] .…”
Section: Discussionsupporting
confidence: 93%
“…As regard age and sex distribution in our study there were no significant differences among group 1 and group 2, these results were in agreement with Tsai et al, [11] and Ozdemir et al, [12] . In comparison of clinical data of group 1 and group 2, therewere no statistical significant differences between the two groups regarding height, systolic blood pressure and diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there have been many advances in the treatment of end-stage renal disease (ESRD), mortality rates for ESRD patients remain several times higher than those of age-matched controls, and patients with ESRD continue to have significant impairments in quality of life (QOL), quality of life is related with morbidity and mortality in hemodialysis patients, and it is suggested that QOL should be considered in the regular monitoring of dialysis patients [4]. Hemodialysis patients infected with HCV often have poor shortterm clinical outcome, greater mortality, greater hospitalization rate, more significant protein-energy malnutrition and worse health -related quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many advances in the treatment of end-stage renal disease (ESRD), mortality rates for ESRD patients remain several times higher than those of age-matched controls, and patients with ESRD continue to have significant impairments in quality of life (QOL), quality of life is related with morbidity and mortality in hemodialysis patients, and it is suggested that QOL should be considered in the regular monitoring of dialysis patients [4]. Hemodialysis patients infected with HCV often have poor shortterm clinical outcome, greater mortality, greater hospitalization rate, more significant protein-energy malnutrition and worse health -related quality of life [5].The prevalence of HCV infection in patients undergoing dialysis is persistently greater than that in the general population, being endemic in hemodialysis units around the world predominantly in Mediterranean and developing countries of the Middle and Far East [6]. It was well demonstrated that HCV had a negative impact on health-related quality of life (HRQOL).…”
mentioning
confidence: 99%